SNACK BEHAVIOUR OF ELEMENTARY SCHOOL STUDENTS IN BLANG MANGAT SUB-DISTRICT, LHOKSEUMAWE CITY - Said Taufiq (Jurnal Scientia, 2023)
The study aimed to get an overview of the snacking behaviour of elementary school children in the Blang Mangat District Area of Lhokseumawe City. The research was quantitative with a descriptive survey method, conducted on 4 bases from July to December 2022. Samples of 288 people were taken using the Cluster Sampling technique. Data collection using questionnaires asked directly to selected respondents. Descriptive data analysis is presented in the form of tables and graphs. The results showed that respondents were predominantly female (52.4%), parental education was the highest school (51.4%) and private employment (83.7%). Pocket money is earned by 97% of children every day, with a frequency of once per day (90%) and an average pocket money of Rp. 5,000-10,000 (48.7%). There 14.9% of students bring lunch to school and generally (69.1%) buy snacks outside the school fence. Children buy a lot of food in the form of and noodles (68.8%) and tea drinks and syrup (79.8%). Students >80% do not wash their hands before and after eating and only about 30% of students consume food using clean spoons and containers. Conclusion Elementary school children in Blang Mangat sub-district almost all always get pocket money and only a few are provided with food from home. Children who bring provisions tend to eat healthy and nutritious food. Food and beverage snacks generally contain harmful food additives, both processed and packaged. Predominantly children buy snacks outside the school fence, consume them by hand and do not wash their hands before and after eating.